Interstitial lung abnormalities and self-reported health and functional status - Axelsson, Gisli Thor (Thorax, 2018)
We investigated the association between interstitial lung abnormalities (ILA) and self-reported measures of health and functional status in 5764 participants from the Age, Gene/Environment Susceptibility-Reykjavik study. The associations of ILA to activities of daily living (ADLs), general health status and physical activity were explored using logistic regression models. Participants with ILA were less likely to be independent in ADLs (OR 0.70; 95% CI 0.55 to 0.90) to have good or better self-reported health (OR 0.66; 95% CI 0.52 to 0.82) and to participate in physical activity (OR 0.72; CI 0.56 to 0.91). The results demonstrate ILA’s association with worsening self-reported health and functional status.